ANIONIC POLYMERIZATION INITIATOR - YAMAUCHI MICHIKAZU; NATORI ITARU (1998)
PROBLEM TO BE SOLVED: To obtain the subject new highly active polymerization initiator capable of readily controlling the molecular weight and using a wide range of copolymerization components. SOLUTION: This polymerization initiator is used for producing a polymer having a polymeric main chain represented by formula I [monomer units A to E may each be arranged in any sequence; (a) to (e) are each wt.% of the monomer units A to E based on the total weight of the monomer units A to E; A is a cyclic conjugated diene-based monomer unit; B is a chainlike conjugated diene-based monomer unit; C is a vinyl aromatic monomer unit; D is a polar monomer unit; E is one or more monomer units selected from an ethylenic and an α-olefinic monomer units; (a+b+c+d+e) is 100; 0<=(a), (b), (c), (d) and (e)<=100] and has 100-5,000 number-average molecular weight expressed in terms of the standard polystyrene. The reactional active center is an organometallic complex represented by formula II [(n) is an integer of 1-4; R is a compound, etc., having the polymeric main chain represented by formula I; R is hydrogen, a halogen, etc.; M<+> is a cation of a group IA metal of the periodic table; X is an organic compound containing one or more of O, N and P] and formula III [(m) is an integer of >=2].